Community voices on climate, peace and security: Kenya - Medina, Leonardo; Souza de Matos, Vanessa; Owuonda, Salome; Lekaram, Alex; Caroli, Giulia; Belli, Anna; Unverdorben, Oliver; Ohenjo, Nyang'ori; Kenduiywo, Benson; Liebig, Theresa Ines; Pacillo, Grazia; Läderach, Peter R.D.; et al. (CGIAR FOCUS Climate Security, 2023)
This study conducted a participatory appraisal of climate vulnerabilities and conflict risks three communities across Kenya: 1) members of the Yiaku Indigenous Peoples in the Mukogodo Forest region, located in Laikipia County; 2) members of the Endorois Indigenous Peoples in the Lake Bogoria Game Reserve region, located in Baringo County; and 3) members of the Banyala Indigenous Peoples at the shores of Lake Victoria, in Busia County. The effects of climate variability across Kenya are contributing to depleting the natural resource base on which many livelihoods rely. Under contexts where hostile relations prevail across neighbouring communities, exacerbated a sense of insecurity in the everyday lives of resource-dependent populations. Six climate security pathways, as experienced by local populations, are identified and discussed within the report. Conflict-sensitive resilience building action urgently needs to be deployed in accordance with community-level priorities, in a way that builds upon local and Indigenous knowledge, everyday experience of problem dynamics, and perceptions around structural sources of vulnerability and conflict. Community members developed context-specific policy recommendations to turn climate-related security risks into opportunities for resilience and peacebuilding. These recommendations are discussed in detail.